KANDUNGAN KLOROFIL DALUGHA (CYRTOSPERMA MERKUSII (HASSK.) SCOTT) PADA HUTAN RAWA PASANG SURUT DI DESA LAINE, PULAU SANGIHE - Ratag, Semuel P.; Pangemanan, Euis F.S.; Tasirin, Johny S. (Universitas Sam Ratulangi, 2017)
ABSTRACT This article is to present the adaptation capacity of Dalugha (giant taro, Cyrtosperma merkusii) indicated by chlorophyll contents at a number of places in Laine Village, Sangihe Island. The study is related to the development of Dalugha as an alternative food plant and its adaptation to the inundated brackish water as a result of raising sea water surface on climate change. The aim of the study is to analyze the differences in chlorophyll contents of inundated and non inundated brackish water conditions in a tree shaded and non shaded conditions. The method is observational where plant responses are observed at the variation created by natural caused. The result showed cthat Dalugha chlorophyll content was influenced by tree shading but it is not influenced by inundation of brackish water. Keywords: dalugha, chlorophyll, tidal swamp forest